The outbreak of artisanal and small-scale gold mining (galamsey) operations in Ghana: Institutions, politics, winners and losers - Issah Baddianaah; Bernard Nuoleyeng Baatuuwie; Raymond Adongo (Brawijaya University, 2022)
This paper focuses on the outbreak of illegal mining (galamsey) operations in Ghana in recent times claiming that the outbreak is accompanied by massive environmental destruction including pollution of water bodies, degradation of farmlands and forest landscapes. Despite the efforts of governmental, non-governmental and civil society organisations to streamline the artisanal and small-scale (ASM) sector since 2017, illegal mining activities remain a livelihood strategy for several Ghanaians. Institutions, politics and local manoeuvrings have rejuvenated and shaped by illegal mining activities. This study employs the narrative review approach to theorize and analyse the pertinent issues influencing the outbreak of ASM activities in Ghana. We draw on the extant theoretical and empirical perspectives to argue that illegal mining activities persist in Ghana today because every stakeholder wants to be a winner–the state institutions are weakened by politics for political triumphs. The local authorities collaborate and embrace illegal mining activities for economic gains while the local communities perceived illegal mining as a last resort to circumventing dispossession by state institutions and foreign mining conglomerates of their share of the mineral wealth. We posited that until the local communities’ share of mineral wealth is duly served them including desirable compensation regimes, illegal mining activities would continue to flourish in Ghana. It is therefore, suggested that mineral resource decisions in the country must identify and incorporate the needs of the local communities. Further research into the needs of local communities, expectations and challenges regarding mineral resources extraction within their range is pertinent.